PRESCRIPTION PATTERN IN COVID-19 PATIENTS ADMITTED TO A TERTIARY CARE CENTER IN KERALA - SUSAN JOSEPH,; SAINATHAN R, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study were to analyze the prescribing pattern in COVID-19 patients and to identify the most commonly prescribed drugs and their routes. Methods: A hospital-based retrospective observational study was conducted based on data of COVID-19 positive patients admitted over a period of 6 months, from May 1, 2020, to October 31, 2020. Relevant data were collected from medical records library. Results: The prescriptions of 1223 COVID-19 positive patients were analyzed. Among them 63.7% were men (n=780). The mean age was 46.5 years. 49.9% (n=611) of our patients were mild cases, categorized as category A. 41.2% (n=505) were category B, and 8.7% came under the severe disease category C. Duration of hospital stay of the patients ranged from 1 to 44 days with a mean duration of 9 days. The most prescribed medication was paracetamol which was prescribed to 55% (n=679) of patients. From the 488 (39.9%) patients who received some antibiotic, the most frequently prescribed was azithromycin (80.1%) followed by ceftriaxone (17.2%) and cefotaxime (3.07%). 18.5% of patients were prescribed anticoagulants, the most common being LMWH-enoxaparin. 17.9% of patients received some systemic corticosteroids. Antivirals prescribed were favipiravir (7.4%), oseltamivir (4.7%), and 0.8% remdesivir. Conclusion: Different drugs belonging to different groups have been prescribed, for symptomatic treatment of disease and its complications as a single effective drug has not been discovered. Almost all the drugs prescribed were generic drugs and were from the Essential List of Medicines-2015.